The Quality of Service and Customer Learning as well as the Influence of Reciprocal Satisfaction and Corporate Image - Nasrul (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to examine the effect of service quality and customer learning on customer satisfaction and corporate image as well as the reciprocal influence between customer satisfaction and corporate image particularly on a government bank in Southeast Sulawesi. This study involved 4 research variables namely service quality, customer learning, customer satisfaction, and corporate image. First of all is Service Quality. Parasuraman, et al., (1988) believed that the Quality of Service is the focus of assessment that replicates customer perceptions on five indicators of Service Quality such as tangible, reliability, responsiveness, assurance, and empathy. These indicators are then used by customers to assess the level of Service Quality at Government Banks in Southeast Sulawesi Province. The indicators to measure Service Quality are adopted from Parasuraman et al., (1985, 1988, 1991) consisting of physical evidence, reliability, responsiveness, assurance, and empathy.(1) It is found that to provide a satisfaction to customers who can further improve the corporate image, the Bank does not only improve the service quality but also providing deeper education to customers more comprehensively. (2) This study shows that the originality of this research is the addition of Customer Learning variable related to mutual satisfaction and image. Customer learning which consists of Customer Ability, Information, and Learning Methods have a significant influence on this commitment. This is a new finding in this study. The Customer Learning at Government Banks is intended to make customers able to utilize the facilities especially modern facilities that have been prepared so that transactions become easier and faster.This research is a development research that develops the variables from several previous studies. The originality of this research is the addition of Customer Learning variables that are related to customer satisfaction which then connect to a corporate image that the authors have not found in other studies. This study also uses the reciprocal relationship between customer satisfaction and corporate image. Previously, some researchers have examined the influence of corporate image which has a significant and positive influence on customer satisfaction.